Henry M. Robert papers - Robert, Henry M. (Henry Martyn), 1837-1923.
Correspondence, letterbooks, memoranda books, diaries, subject files, and other papers relating chiefly to Robert's career in the U.S. Army Corps of Engineers and as a parliamentarian. Documents his service as engineer commissioner of the District of Columbia and the publication of his Pocket Manual of Rules of Order for Deliberative Assemblies (1876) commonly known as Robert's Rules of Order. Also documents engineering projects on the Delaware River (Ky. and Tenn.) and Cumberland River (N.Y.-Del. and N.J.), and in Frontera, Mexico, Galveston, Tex., Milwaukee, Wis., and New Bedford, Mass. Includes material pertaining to Robert's involvement in the Baptist Church. Correspondents include Newton R. Collamer, Mary Innis Denton, Persifor Frazer, James Allen Hardie, Lewis M. Haupt, A.A. Humphreys, Edward Judson, George H. Mendell, Joseph Thomas Robert, Joseph Gilbert Totten, Edward T. Townsend, John M. Wilson, and S.C. Griggs & Co.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Army officer, engineer, and parliamentarian.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Collamer, Newton R. -- Correspondence; Denton, Mary Innis -- Correspondence; Frazer, Persifor, -- 1844-1909 -- Correspondence; Hardie, James Allen, -- 1823-1876 -- Correspondence; Haupt, Lewis M. -- 1844- -- Correspondence; Humphreys, A. A. -- 1810-1883 -- Correspondence; Judson, Edward, -- 1844-1914 -- Correspondence; Mendell, George H. -- 1831-1902 -- Correspondence; Robert, Henry M. -- 1837-1923.; Robert, Henry M. -- 1837-1923.; Robert, Joseph Thomas, -- 1835-1925 -- Correspondence; Totten, Joseph Gilbert, -- 1788-1864 -- Correspondence; Townsend, Edward T. -- Correspondence; Wilson, John M. -- 1837-1919 -- Correspondence; United States. -- Army. -- Corps of Engineers; S.C. Griggs & Co. -- Correspondence; Baptists; Engineering -- Cumberland River (Ky. and Tenn.); Engineering -- Delaware River Valley (N.Y.-Del. and N.J.); Engineering -- Massachusetts -- New Bedford; Engineering -- Mexico -- Frontera; Engineering -- Texas -- Galveston; Engineering -- Washington (D.C.); Engineering -- Wisconsin -- Milwaukee; Military engineering; Parliamentary practice; Army officers; Engineers; Parliamentarians